2017
DOI: 10.1083/jcb.201704179
|View full text |Cite
|
Sign up to set email alerts
|

mTORC in β cells: more Than Only Recognizing Comestibles

Abstract: Maedler and Ardestani discuss recent work from Chau et al. on the role of mTOR for β cell survival in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…b cell-specific activation of mTORC1 in genetic mouse models found that hyperactivation of mTORC1 signaling resulted in increased b cell function and improved glucose tolerance (Blandino-Rosano et al, 2017;Hamada et al, 2009;Mori et al, 2009;Rachdi et al, 2008;Shigeyama et al, 2008). Consistently, b cell-specific ablation of mTORC1 resulted in lower insulin secretion caused by mitochondrial dysfunction and oxidative stress, indicating that mTORC1 activity is essential for b cell function and maturation (Sinagoga et al, 2017;Chau et al, 2017;Ardestani et al, 2018;Maedler and Ardestani, 2017;Ni et al, 2017;Blandino-Rosano et al, 2017;Alejandro et al, 2017). In contrast, other findings show that chronically increased mTORC1 activity can induce b cell failure (Mori et al, 2009;Sun et al, 2010;Swisa et al, 2015;Elghazi et al, 2010;Bartolome and Guillé n, 2014;Koyanagi et al, 2011;Jaafar et al, 2019).…”
Section: Context and Significancementioning
confidence: 93%
“…b cell-specific activation of mTORC1 in genetic mouse models found that hyperactivation of mTORC1 signaling resulted in increased b cell function and improved glucose tolerance (Blandino-Rosano et al, 2017;Hamada et al, 2009;Mori et al, 2009;Rachdi et al, 2008;Shigeyama et al, 2008). Consistently, b cell-specific ablation of mTORC1 resulted in lower insulin secretion caused by mitochondrial dysfunction and oxidative stress, indicating that mTORC1 activity is essential for b cell function and maturation (Sinagoga et al, 2017;Chau et al, 2017;Ardestani et al, 2018;Maedler and Ardestani, 2017;Ni et al, 2017;Blandino-Rosano et al, 2017;Alejandro et al, 2017). In contrast, other findings show that chronically increased mTORC1 activity can induce b cell failure (Mori et al, 2009;Sun et al, 2010;Swisa et al, 2015;Elghazi et al, 2010;Bartolome and Guillé n, 2014;Koyanagi et al, 2011;Jaafar et al, 2019).…”
Section: Context and Significancementioning
confidence: 93%
“…Although no studies have been conducted in β cell, mTORC1 is ordinarily inhibited under oxidative stress, potentially through the activation of AMPK [82]. The inactivation of mTORC1 may have several detrimental effects (Figure 2), the first of which is the increased expression of Thioredoxininteracting protein (TXNIP) and shuttling of it into the mitochondria under oxidative stress conditions [85][86][87]. TXNIP is a ubiquitously expressed protein that influences cellular redox balance through negatively regulating the TXN antioxidant systems [88].…”
Section: Mtor Inhibitionmentioning
confidence: 99%
“…For example, it has been demonstrated that β-cell-specific loss of mTORC1 causes DM and β-cell failure due to defects in proliferation, autophagy, apoptosis, and insulin secretion in mice [96]. Furthermore, β cell specific mTOR KO mice as well as mTOR deficient β cell line has revealed compromised mitochondrial membrane potential and respiration, which lead to impaired ATP production, lower intracellular Ca 2+ levels, impaired insulin secretion, and ROS production [87]. mTOR has also been shown to be important to maintain β cell mature identity and to suppress α cell enriched genes including MAF BZIP transcription factor B (MafB), suggesting a potential role of oxidative stress in β cell dedifferentiation [97].…”
Section: Mtor Inhibitionmentioning
confidence: 99%
“…Other researchers suggest that the role of glucose and amino acids in the activation of mTORC1 is mediated by an increase in mitochondrial metabolism, even in MIN6 cells. Several studies confirm the link between mTOR signaling, mitochondrial activity, and insulin production [46,61,62]. Nevertheless, to determine the exact molecular pathways that bring about the effects of BF142 requires further investigations.…”
Section: Plos Onementioning
confidence: 97%